PROSEDUR KERJA PRAMUSAJI DI SELERA RESTORAN NONGSA POINT MARINA & RESORT BATAM - Andhira, Ayu (RC-INSTITUT, 2019)
This study aims to find out the procedure of serving tastes in restaurant tastes Nongsa Point Marina & Resort Batam this type of research is descriptive reserch with qualitative methosd. Data collection techniques used were interview, observation, and documentation methods. The data analysis technique used is qualitative data analysis. From the results of the study found several things related to the waiitress working procedures in the tastes of the restaurant Nongsa Point Marina & Resort Batam, namely: by following good standard procedures and a sense of belonging and a standard sense of beloging and a standard sense of work procedures with provisions that have been made will make the waiter be professional in his field.